2019
DOI: 10.4236/jep.2019.105037
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies on the Microbial Degradation of Plastic Waste Using <i>Aspergillus niger</i> and <i>Pseudomonas</i> sp.

Abstract: The possibility of microbial degradation of plastic waste was investigated by isolating microorganisms present in dumpsite containing low-density polyethylene (LDP). Aspergillus niger (fungi) and Pseudomonas sp. (bacteria) were identified and subsequently used to biodegrade plastic waste. The medium was made up of 0.2 g of MgSO 4 , 1.0 g of KH 2 PO 4 , 1.0 g of K 2 HPO 4 , 1.0 g of NH 4 NO 3 , 0.02 g of CaCl 2 , 0.05 g of FeCl 3 in 1000 ml water. 10 ml of the medium containing the bacteria and/or fungi was pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…According to the study of Robert et al [17], the consortium of five strains containing Pseudomonas and Bacillus species grew synergistically in the presence of polyethylene terephthalate and the cleavage product bis (2-hydroxy ethyl) terephthalic acid (BHET) as sole source of carbon. This is also in line with the study of Ogunbayo et al, [18] in which consortium of microorganisms was reported to have higher degradation efficacy. The higher degradation by consortium of these organisms can be attributed to the synergistic activity of these microorganisms in degradation of polyethylene.…”
Section: Resultssupporting
confidence: 92%
“…According to the study of Robert et al [17], the consortium of five strains containing Pseudomonas and Bacillus species grew synergistically in the presence of polyethylene terephthalate and the cleavage product bis (2-hydroxy ethyl) terephthalic acid (BHET) as sole source of carbon. This is also in line with the study of Ogunbayo et al, [18] in which consortium of microorganisms was reported to have higher degradation efficacy. The higher degradation by consortium of these organisms can be attributed to the synergistic activity of these microorganisms in degradation of polyethylene.…”
Section: Resultssupporting
confidence: 92%
“…All the representative bacterial isolates (n= 54) were used for the plastic biodegradation assay for periods of 15, 30, 45, and 60 d, using the method described by Ogunbayo et al, (2019) with slight modifications. The collected plastics bags and bottles were cut into tiny square strips (1×1 cm) using a sterile pair of table scissors.…”
Section: Biodegradation Of the Plastic Materialsmentioning
confidence: 99%
“…The same steps were repeated for all the treated samples in duplicates. The percentage of degradation (%) of each strip of bags and bottles by the tested bacteria was determined through calculating the % of weight loss of the plastic materials using the following formula of Ogunbayo et al, (2019):…”
Section: Biodegradation Of the Plastic Materialsmentioning
confidence: 99%
“…The process of a polymer's chemical structure changing from a more complex to a simpler one under the influence of several biological agents, such as bacteria, fungi, and various atmospheric microorganisms, is known as biodegradation 6 . More than 90 genera of microorganisms that break down polymers such as: Actinomycetes, Thermoactinomyces, Azotobacter, Alcaligenes, Streptomyces, Mycobacterium, Micromonospora, Flavobacterium, Escherichia, Rhodococcus, Streptococcus, Klebsiella, Nocardia, Pseudomonas, Comamonas, and Staphylococcus 7,8 . The plastic biodegradation mechanism involves many levels.…”
Section: Introductionmentioning
confidence: 99%